Low temperature stress dictates the success of rice fallow sesame in Odisha - An analysis: Low temperature stress dictates the success of rice fallow sesame in Odisha - An analysis - K RAMESH; ANITA MOHAPATRA; B C DHIR; A VISHNUVARDHAN REDDY (Journal of Oilseeds Research, 2020)
Rice fallow areas are the potential regions for extending the oilseed area horizontally to utilize the residual moisture and nutrients. The temperature regimes in the region dictates sesame sowing. An analysis of the temperature profile in the chief sesame growing region viz., Mahisapet (Dhenkanal) has indicated that the minimum temperature prevailed during the months of December and January provides low temperature induced stress for sesame in this region. The minimum temperature recorded during the month of December during 2016, 2017 and 2018 were 15.4, 13.2 and 13.7°C respectively, while in January it still dropped to 13.5, 11.1 and 11.5°C respectively. Concerted research efforts are needed to develop new technologies for this low temperature management.